How Do People Come to Judge What Is "Reasonable"? Effects of Legal and Sociological Systems on Human Psychology. (March 2023) - Spruill, Mikaela; Lewis, Neil A.
How do people decide what is reasonable? People often have to make those judgments, judgments that can influence tremendously consequential decisions—such as whether to indict someone in a legal proceeding. In this article, we take a situated cognition lens to review and integrate findings from social psychology, judgment and decision-making, communication, law, and sociology to generate a new framework for conceptualizing judgments of reasonableness and their implications for how people make decisions, particularly in the context of the legal system. We theorize that differences in structural and social contexts create information asymmetries that shape people's priors about what is and is not reasonable and how they update their priors in the face of new information. We use the legal system as a context for exploring the implications of the framework for both individual and collective decision-making and for considering the practical implications of the framework for inequities in law and social policy.